Acquired Immunodeficiency Syndrome Presented as Atypical Ocular Toxoplasmosis. (3rd May 2021) - Khalili Pour, Elias; Riazi-Esfahani, Hamid; Ebrahimiadib, Nazanin; Esteghamati, Violet Zaker; Zarei, Mohammad
Abstract : Background . The aim is to report an atypical presentation of ocular toxoplasmosis which led to the diagnosis of Acquired Immunodeficiency Syndrome (AIDS). Case Report . The 38-year-old woman was referred with metamorphopsia and reduced vision in the right eye over the past 3 weeks. Slit-lamp examination revealed granulomatous keratic precipitates (KPs), 2+ cells in the anterior chamber, and posterior synechiae. Fundus examination was remarkable for a white patch surrounding a scar, inferonasal to the optic disc with fibrous bands emanating from the lesion, and the retina around this region was detached with considerable extension towards the periphery, while no breaks could be appreciated. She mentioned anorexia and losing 10 kg in the past three months, and signs of anemia like paleness of face skin, bed nails, and bilateral angular cheilitis were observed on systemic evaluation. The results of the patient's complete blood count revealed anemia and leukopenia and CD4 lymphocytes: 79 cells/ μ L. Enzyme-linked immunosorbent assays (ELISA) for HIV antibodies came back positive which was later confirmed with the Western blot test. Brain magnetic resonance imaging (MRI) showed multiple ring-enhancing lesions in both cerebral cortices. The patient underwent antitoxoplasmosis and anti-HIV treatment and serous retinal detachment completely resolved. Conclusion . This report highlights the fact that sometimes, the eyes are the site of the first presentation of a systemic life-threatening condition and emphasizes the role of ophthalmologists in such cases. In cases of atypical presentation, appropriate laboratory tests and CNS imaging should be requested. Systemic treatment with antitoxoplasmosis regimens and highly active antiretroviral therapy (HAART) is mandatory in AIDS patients with ocular toxoplasmosis.